Economy-wide and Sectoral Impacts on Workers of Brazil's Internet Rollout - Dutz, Mark A.; Ferreira Mation, Lucas; O'Connell, Stephen D.; Willig, Robert D. (Taylor and Francis, 2017)
We study the effect of Brazil’s staggered Internet rollout between 2000 and 2014 on municipality employment and wages. We use a new annual data-set on Internet availability from the Brazil school census, with the assumption that the share of schools that have Internet access in each municipality reflects general accessibility of Internet connections. We combine these data with Brazil’s rich matched employer–employee survey (RAIS), which contains annual occupation and wage earnings information for all formally employed workers in Brazil across all sectors, including primary, secondary, and tertiary industry groups. We consider both contemporaneous and lagged effects. We find that increased Internet access has no statistically significant net effect on aggregate employment and has a negative effect on average wages, with a reduction in measures of wage dispersion. Brazil’s Internet rollout results in employment shifts from sectors with more limited expansion opportunities (wholesale and retail trade, public administration and largely publicly owned utilities, that jointly comprise almost half of the formal workforce in 2010) to sectors with more output expansion opportunities. Employment effects are positive and most pronounced in manufacturing, transport and storage, finance and insurance, and hospitality industry groups. In the manufacturing sector, Internet access induces positive employment and wage effects in both medium- and high-skill occupations.